A LAST GASP FOR SMOKERS ON AIRLINERS? - DEAN,P (Tufts Archival Research Center, 2007)
Printout of a Los Angeles Times article on the consequences of a proposed Congressional ban on smoking on flights 2 hours or less. Deems total ban inevitable within 5 years. Summarizes studies on effects of secondhand smoke in airplanes. Discusses trends in airline smoking policies. Presents the Tobacco Institute belief that in-flight smoking has no negative health effects to nonsmokers and that the bill will be defeated. Illustrates the important role of flight attendants.